Clinical, environmental and histological distribution of BRAF, NRAS and TERT promoter mutations among patients with cutaneous melanoma: a retrospective study of 563 patients. (21st July 2020) - Manrique‐Silva, E.; Rachakonda, S.; Millán‐Esteban, D.; García‐Casado, Z.; Requena, C.; Través, V.; Kumar, R.; Nagore, E.
Summary: Background: The distinct somatic mutations that define clinical and histopathological heterogeneity in cutaneous melanoma could be dependent on host susceptibility to exogenous factors like ultraviolet radiation. Objectives: Firstly, to characterize patients with cutaneous melanoma clinically and pathologically based on the mutational status of BRAF, NRAS and TERT promoter. Secondly, to elucidate the modified features due to the presence of TERT promoter mutations over the background of either BRAF or NRAS mutations. Methods: We performed a retrospective study on 563 patients with melanoma by investigating somatic mutations in BRAF, NRAS and TERT promoter. Results: We observed co‐occurrence of TERT promoter mutations with BRAF and NRAS mutations in 26.3% and 6.9% of melanomas, respectively. Multivariate analysis showed an independent association between BRAF mutations and a decreased presence of cutaneous lentigines at the melanoma site, and an increased association with the presence of any MC1R polymorphism. We also observed an independent association between TERT promoter mutations and increased tumour mitotic rate. Co‐occurrence of BRAF and TERT promoter mutations was independently associated with occurrence of primary tumours at usually sun‐exposed sites, lack of histological chronic sun damage in surrounding unaffected skin at the melanoma site, and increased tumour mitotic rate. Co‐occurrence of NRAS and TERT promoter mutations was independently associated with increased tumour mitotic rate. The presence of TERT promoter together with BRAF or NRAS mutations was associated with statistically significantly worse survival. Conclusions: The presence of TERT promoter mutations discriminates BRAF ‐ and NRAS ‐mutated tumours and indicates a higher involvement of ultraviolet‐induced damage and tumours with worse melanoma‐specific survival than those without any mutation. These observations refine classification of patients with melanoma based on mutational status. Abstract : What is already known about this topic? Mutations in TERT promoter, BRAF and NRAS constitute the most frequent driver alterations in melanoma. Noncoding TERT promoter mutations increase TERT expression and synergistically influence the effect of BRAF and NRAS on patient survival and modify associations with different clinical and tumour characteristics. What does this study add? We have shown differences in BRAF ‐ and NRAS ‐mutated tumours associated with concomitant presence of TERT promoter mutations. The presence of TERT promoter mutations together with either BRAF or NRAS mutation resulted in an increased association with ultraviolet‐induced damage and poor prognosis. The poor prognosis was more pronounced in tumours with TERT promoter mutations over the background of NRAS than BRAF mutations. What is the translational message? Activating BRAF and NRAS mutations are frequent in melanomas but are not sufficient to drive malignant transformation, and require additional genetic events. Co‐occurrence of TERT promoter mutation with BRAF and NRAS alterations correlates with poor prognosis, with a demonstrated functional link between mitogen‐activated protein kinase signalling and telomerase reactivation, which could have potential clinical implications. Pertinently, the largest subgroup of patients had no mutations at any of the three investigated loci and had demonstrably better disease outcome. Linked Comment:  Sheen and Chu. Br J Dermatol 2021; 184:390–391 . Plain language summary available online